High-rate and durable aqueous zinc ion battery using dendritic V10O24·12H2O cathode material with large interlamellar spacing. (10th October 2018) - Wei, Tongye; Li, Qian; Yang, Gongzheng; Wang, Chengxin
Abstract: Rechargeable aqueous zinc-ion batteries (ZIBs) are very promising energy storage systems owing to their low cost, high reliability, and high volumetric energy density; however, the stiff challenge for the progress of ZIBs is the lack of suitable materials that permit divalent ion-intercalation/deintercalation with fast kinetics, long cycling durations, and high rate capabilities. Herein, we demonstrate V10 O24 ·12H2 O dendrites with a large interlayer spacing of 1.4 nm, fabricated through a simple hydrothermal method. The unique, open, and stable structure complemented by a mixed valence enables a satisfactory battery performance: a specific capacity of 164.5 mAh g −1, long-term cycling stability of 80.1% capacity retention after 3000 cycles, and high power density of 12247.8 W kg −1 at a high energy density of 88.5 Wh kg −1 . This study provides a viable and attractive cathode material for practical ZIBs.